The relationship between effort-reward imbalance and burnout among sport coaches: the moderating role of over-commitment and job control - Jang, D.; Yan, C.; Won, J.; Lee, S.; Fang, L. (International Journal of Sport and Exercise Psychology, 2025)
This study investigated the relationship between effort-reward imbalance and burnout among sport coaches, as well as the potential moderating effects of over-commitment and job control. Four hundred and fifty sports coaches in the elite system from China completed self-report questionnaires measuring effort-reward imbalance, over-commitment, job control, and coach burnout. After data screening, 438 participants were included in the analysis. An additive multiple moderation analysis was conducted to examine the effect of the interaction between effort-reward imbalance, over-commitment, and job control on burnout. The results showed that effort-reward imbalance and over-commitment were positively associated with burnout, while job control was negatively associated. Moreover, the relationship between effort-reward imbalance and burnout was significantly moderated by both over-commitment and job control. Whereas over-commitment strengthened this association, job control buffered it. These findings suggest that interventions aimed at reducing over-commitment and improving job control may help prevent burnout among sports coaches, especially those experiencing high levels of effort-reward imbalance.